Surgical Removal Of Urolith By Prescrotal Urethrotomy In A Bull: A Case Report - Pal, Madan; Saharan, Sandeep; Dinesh; Potliya, Sandeep; Kumar, Kailash; Kumar , Sarvan (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Urolithiasis is a major disease of domestic animals all over the world. Uroliths occur in either sex, but obstructive urolithiasis is primarily a problem of male due to anatomical conformation of their urinary tract (Larson, 1996). Various factors influences the formation of stone in the urinary tract like diet, age, sex, breed, genetic makeup, season, soil, water, hormone levels, mineral and infection (Kalim et al., 2011). Once the calculi are formed in urinary tract, they may be lodged in any part of the urinary tract, thus leading to the retention of urine causes bladder distention, abdominal pain and eventual urethral perforation or bladder rupture with death from uremia or septicemia (Gasthuys et al., 1993). Urolithiasis is seen most often during winter and during severe weather conditions with limited water intake, especially when the water has a high mineral content. In male ruminants the urethral diameter becomes progressively smaller from the ischial arch toward the tip of the penis. The calculi most commonly lodge in the urethra at the distal sigmoid flexure where there is pronounced narrowing of the urethral diameter (Wolfe and Moll, 1998).